Antifungal and anti-biofilm effect of the calcium channel blocker verapamil on non-albicans candida species - Scorzoni, Liliana [UNESP]; de Menezes, Raquel T. [UNESP]; Pereira, Thais C. [UNESP]; Oliveira, Priscila S. [UNESP]; Ribeiro, Felipe de Camargo [UNESP]; Santos, Evelyn Luzia de Souza [UNESP]; Fugisaki, Luciana R. O. [UNESP]; de Oliveira, Luciane D. [UNESP]; Amorim, José Benedito O. [UNESP] (FapUNIFESP (SciELO), 2020)
Candida is a human fungal pathogen that causes a wide range of diseases. Candida albicans is the main etiologic agent in these diseases; however, infections can be caused by non-albicans Candida species. Virulence factors such as biofilm production, which protect the fungus from host immunity and anti-fungal drugs, are important for the infection. Therefore, available antifungal drugs for candidiasis treatment are limited and the investigation of new and effective drugs is needed. Verapamil is a calcium channel blocker with an inhibitory effect on hyphae development, adhesion, and colonization of C. albicans. In this study, we investigated the effect of verapamil on cell viability and its antifungal and anti-biofilm activity in non-albicans Candida species. Verapamil was not toxic to keratinocyte cells; moreover, C. krusei, C. parapsilosis, and C. glabrata were susceptible to verapamil with a minimal inhibitory concentration (MIC) of 1250 μM; in addition, this drug displayed fungistatic effect at the evaluated concentrations. After treatment with verapamil, reduced viability, biomass, and mitochondrial activity were observed in biofilms of the non-albicans Candida species C. krusei, C. glabrata, and C. parapsilosis. These findings highlight the importance of the study of verapamil as an alternative treatment for infections caused by non-albicans Candida species.
Keywords: Antifungal activity; Biofilm; Candida non-albicans; Drug repurposing; Verapamil